The Impact of Firm Size, Capital Structure, and Good Corporate Governance on Dividend Policy in Manufacturing Companies Listed on the IDX from 2019-2023 - Mahendra, Heru; Kusmayadi, Iwan (Indonesian Journal of Advanced Research, 2025)
The study examines the impact of company size, capital structure, and good corporate governance (GCG) on the dividend policy of manufacturing companies listed on the IDX from 2019-2023. Using purposive sampling, 15 out of 164 companies were analyzed with regression and panel data methods via EViews 13. The results show that company size (total assets) negatively affects the dividend payout ratio (DPR), though insignificantly. Capital structure (debt-to-equity ratio) has a positive and significant effect on DPR, while GCG (total audit committee) has a negative but insignificant effect. These findings provide insights for stakeholders in formulating policies to attract investors, enhance the capital market, and support the manufacturing sector’s growth, contributing to national economic development.